Insulation conductivity diagnostic of polymer nanocomposite material for high voltage applications [electronic resource] - Muhammad Ahmad, 1988; Mohamed Afendi Mohamed Piah (2014)
Thesis (Sarjana Kejuruteraan (Elektrik - Kuasa)) - Universiti Teknologi Malaysia, 2014